Advances in the use of topical imiquimod to treat dermatologic disorders - Francesco Lacarrubba; Maria Rita Nasca; Giuseppe Micali (Dove Medical Press, 2008)
Francesco Lacarrubba, Maria Rita Nasca, Giuseppe MicaliDermatology Clinic, University of Catania, ItalyAbstract: Imiquimod (IQ) is an immune-response modifying agent, first approved by FDA for the topical treatment of external genital and perianal warts in 1997. It induces, through stimulation of Toll-like receptors (TLRs) localized on the surface of antigen-presenting cells, synthesis and release of several endogenous pro-inflammatory cytokines such as interferon-α (IFN-α), tumor necrosis factor-α (TNF-α) and interleukins (IL) 6 and 12, which in turn stimulate both the innate and acquired immune pathways, resulting in upregulation of natural antiviral and antitumor activity. IQ 5% cream has been used for the treatment of a wide variety of dermatologic conditions in which the immune system is thought to play a role in regression of the disease. In some disorders, such as genital and perianal warts, actinic keratoses, basal cell carcinomas, Bowen’s disease and molluscum contagiosum, relative safety and efficacy are supported by randomized controlled trials of IQ. However, it is common for patients to experience local skin reactions, which can range from mild to severe in intensity, but usually resolve 1–2 weeks after interrupting treatment. Additional randomized trials are encouraged to assess safety and efficacy of IQ in the treatment of an even wider range of cutaneous disorders.Keywords: imiquimod, immune response modifiers